Development of the "GAULL" Mathematics Learning E-Module Using Crossword Games on Flat-side Space Buildings - Hasan, Regina Trichianitha Salchabila; Machmud, Tedy; Pauweni, Khardiyawan A. Y.; Ismail, Sumarno (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
Learning media is a very effective for teachers to improve the quality of learning and ensure that students can understand the material better. For this reason, it is necessary to design learning media that can facilitate students to understand the material being studied. This research aims to develop and implement a learning e-module by utilizing crossword games on the subject of flat-sided spatial construction for class VIII junior high school students, through a 4-D development research design, which are define, design (planning), develop (development), and dissiminate (distribution). E-module development utilizes facilities on the Heyzine website and other supporting applications such as Ms Word and Canva. The subjects of this research were 27 class VIII students at SMPN 1 Bulawa. The instruments used in this research were a questionnaire for media expert validation, a material expert validation questionnaire, a teacher respondent questionnaire and a student respondent questionnaire. The media expert validation results got a score of 3.55, including very valid criteria, while the material expert validation results got a score of 3.72 with the same criteria, which very valid. The results of the limited scale trial to see practicality through the teacher respondent questionnaire obtained a percentage of 97%, which the very practical criteria, while the student respondent questionnaire obtained a percentage of 93.57%, also included in the very practical criteria. Thus, the e-module developed is declared suitable for use and dissemination.